Use of a capsular tension ring to prevent early postoperative rotation of a toric intraocular lens in high axial myopia. Issue 2 (April 2015) - Safran, Steven G.
Abstract : N/A: Two patients with high axial myopia, bilateral cataracts, and astigmatism had cataract surgery with implantation of a toric intraocular lens (IOL) without a capsular tension ring (CTR) in the first eye. Rotation of the IOL occurred shortly after surgery. In the second eye of both patients, a toric IOL of the same type and power and with a similar axial orientation as in the first eye was used; however, a CTR was placed at the time of surgery. In both cases, there was no IOL rotation in the second eye. Placement of a CTR at the time of cataract surgery in highly myopic eyes may help prevent postoperative rotation of a toric IOL. Financial Disclosure : The author has no financial or proprietary interest in any material or method mentioned.